Household Economic Consequences of Rheumatic Heart Disease in Uganda - Opara, Chinonso C.; Du, Yuxian; Kawakatsu, Yoshito; Atala, Jenifer; Beaton, Andrea Z.; Kansiime, Rosemary; Nakitto, Miriam; Ndagire, Emma; Nalubwama, Haddy; Okello, Emmy; Watkins, David A.; Su, Yanfang (Frontiers in Cardiovascular Medicine, 2021)
Background: Rheumatic heart disease (RHD) has declined dramatically in wealthier countries in the past three decades, but it remains endemic in many lower-resourced regions and can have significant costs to households. The objective of this study was to quantify the economic burden of RHD among Ugandans affected by RHD. Methods: This was a cross-sectional cost-of-illness study that randomly sampled 87 participants and their households from the Uganda National RHD registry between December 2018 and February 2020. Using a standardized survey instrument, we asked participants and household members about outpatient and inpatient RHD costs and financial coping mechanisms incurred over the past 12 months. We used descriptive statistics to analyze levels and distributions of costs and the frequency of coping strategies. Multivariate Poisson regression models were used to assess relationships between socioeconomic characteristics and utilization of financial coping mechanisms. Results: Most participants were young or women, demonstrating a wide variation in socioeconomic status. Outpatient and inpatient costs were primarily driven by transportation, medication, and lab tests, with overall RHD direct and indirect costs of 74 per person-year. Between 20% and 35% percent of households experienced catastrophic healthcare expenditure, with participants in the Northern and Western Regions 5-10 times more likely to experience such hardship and utilize financial coping mechanisms than counterparts in the Central Region, a wealthier area. Increases in total RHD costs were positively correlated with increasing use of coping behaviors. Conclusion: Ugandan households affected by RHD, particularly in lower-income areas, incur out-of-pocket costs that are very high relative to income, exacerbating the poverty trap. Universal health coverage policy reforms in Uganda should include mechanisms to reduce or eliminate out-of-pocket expenditures for RHD and other chronic diseases.